Relevansi Nilai-Nilai Kewirausahaan dalam Materi PAI BP SMA Sederajat K-13 Revisi 2020 - Hamdan Adib (QuranicEdu: Journal of Islamic Education, 2022)
The purpose of this research was to determine the relevance of entrepreneurship values to the material for BP PAI at SMA of K-13 Revised 2020. This research used a qualitative method with the type of literature study. The primary sources in this research were LKS PAI BP SMA and secondary sources were various literatures that supported the research theme. The results of this research indicated that there was a relevance of entrepreneurial values in the BP PAI material in high school, including the material for class X. Chapter 3 described learning obligations where entrepreneurs had to have broad insights, then class XI in Chapter 1 was a work of ethical material that had work orientation. Then the results were in Chapter 10 related to Islamic economics and various economic practices based on the rules of the Qur'an Hadith and other basic Islamic law and class XII in Chapter 1 and Chapter 4 which discussed positive thinking, hard work and responsibility. It was a concrete form of leadership values contained in entrepreneurship.